Les Noces Chymiques de Johann Valentin Andreae dans Die Geheimnisse et Das Märchen de Goethe - Annie Zdenek (Recherches Germaniques)
Goethe considered the Chymical Wedding as a poetic and pleasant work which, in 1784, he decided to rewrite to provide to his contemporaries a modernized version. He did not carry it out but the reading of this esoteric tale led him to the writing of the poem Mysteries (1784-1785), which remained unfinished and was characterized by the rose and the cross. The themes outlined in the Mysteries (such as the idea of beautiful humanity and tolerance) would later permeate Goethe’s work: they can be found in Wilhelm Meister (1795-1796, 1821-1829), and more especially in The Green Snake and the Beautiful Lily (1795) which concludes the Conversations of German Emigrants (1795). Both demonstrate the connection with Rosicrucian bodies of thought. In The Green Snake and the Beautiful Lily, Goethe borrowed alchemical symbols as theologian Andreae did in his esoteric novel and he sometimes parodied them so as to depict the process of development of his characters, but unlike Andreae, Goethe gave them a political and moral meaning: the new historical context of the end of the 18th century, that is to say the French revolution, weakened the German countries and divided the cultivated elite. From then on, for Goethe, the individual and his necessary self-fulfillment could not stand in the foreground anymore, nor could the process of individual education illustrated by the alchemical initiation of the hero: community cohesion now became central. Only the union of all the living forces of the country could lead to the healing of the community. As in Andreae’s work, the god Eros, a creative and stimulating force, was at the heart of the regeneration process.